Effects of a reminiscence therapy-involved program on anxiety, depression, and the quality of life in cancer patients: a meta-analysis of randomized controlled trials - Sun, Xingliang; Su, Wenlian; Yin, Mengyue; Xia, Ling (Frontiers in Psychology, 2024)
Objective: Reminiscence therapy is gradually utilized in cancer patients to address psychological pressure and enhance their quality of life. This meta-analysis aimed to comprehensively evaluate the effect of reminiscence therapy-involved program (RTIP) on anxiety, depression, and quality of life in cancer patients. Methods: A systematic literature search was conducted in the Web of Science, PubMed, Embase, and Cochrane Library databases until December 2023 to screen randomized control trials (RCTs) comparing the effect of RTIP and control care. Results: Sixteen RCTs published in 2013~2023 were included, with 1,963 cancer patients receiving RTIP with or without control care (RTIP group, N=984) or control care (control group, N=979). Anxiety score [standardized mean differences (SMD)=-0.539; 95% confidence interval (CI)=-0.700, -0.378; P<0.001], anxiety rate [relative risk (RR)=0.736; 95%CI: 0.627, 0.865; P<0.001], depression score (SMD=-0.664; 95%CI: -0.967, -0.361; P<0.001), and depression rate (RR=0.632; 95% CI=0.532, 0.750; P<0.001) were reduced in RTIP group compared to control group. Furthermore, overall quality of life was increased in RTIP group than control group (SMD=0.501; 95%CI: 0.314, 0.689; P<0.001). In digestive system cancer patients, anxiety/depression score and rate were reduced, and overall quality of life was elevated in RTIP group versus control group (all P<0.050). Concerning the quality of evidence, the risk of bias was generally low in most studies. No publication bias existed in outcomes (all P>0.050). Conclusion: RTIP attenuates anxiety and depression, and improves quality of life in cancer patients, which is beneficial for the general health condition of cancer patients.